Taxas de matrícula e gastos em educação no Brasil - Maduro Júnior, Paulo Rogério Rodrigues (2007)
In this paper we analyze, in a macroeconomic perspective, the cost of Brazilian low educational attainment. Our approach is based on a version of the neoclassical growth model comprising a mincerian formulation to human capital. By properly parametrizing this model, we could assess the impact of a factible increase of educational expenses on attainment on macroeconomic aggregates from 1933 afterwards. Higher educational expenses would lead to additional enrollments in public schooling and this higher attainment would, in turn, raise labor productivity. Thus, the educational cost per student is required to our analysis and we reproduce then the enrollment number to each schooling level (primary, secondary and tertiary) to each year and the gross enrollment rate from 1933 to 2005; also, we suggest a computation of a historic series of public educational expenses for the same period. Our approach indicates that GDP in 2004 could have been up to 27% higher. Another question we attempt to address is the universalization of primary and secondary education, by the Öfties and sixties. Although such policy would lead to and GDP increase of 26%, in comparison to the one observed by 2004, it would require massive educational expenses, which would be more than 10% of GDP from 1958 to 1962, for instance.